2005
DOI: 10.1016/j.ejcts.2005.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Downsizing of the mitral valve and coronary revascularization in severe ischemic mitral regurgitation results in reverse left ventricular and left atrial remodeling

Abstract: Combined mitral downsizing and CABG surgery was performed with excellent clinical results: only minimal residual MR, a significant reduction of LA dimension and an increase of LV contractility due to reverse remodeling were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 28 publications
1
33
1
Order By: Relevance
“…Hence, annuloplasty successfully reduces MR grade in most patients having surgery for IMR. Furthermore, recent reports document that stringent use of a rigid or semi-rigid, complete annuloplasty ring appears to provide excellent (up to 2 years) freedom from recurrent MR [34][35][36]. It is possible that application of this approach, combined with patient selection based upon identifiable and measurable indices on preoperative echocardiography, will enhance durability of annuloplasty for functional IMR.…”
Section: Durabilitymentioning
confidence: 93%
“…Hence, annuloplasty successfully reduces MR grade in most patients having surgery for IMR. Furthermore, recent reports document that stringent use of a rigid or semi-rigid, complete annuloplasty ring appears to provide excellent (up to 2 years) freedom from recurrent MR [34][35][36]. It is possible that application of this approach, combined with patient selection based upon identifiable and measurable indices on preoperative echocardiography, will enhance durability of annuloplasty for functional IMR.…”
Section: Durabilitymentioning
confidence: 93%
“…The anterior leaflet tethering significantly improved and remained stable in these patients, confirming that it is the augmented and, more important, progressive posterior leaflet tethering that is related to recurrent mitral regurgitation after annuloplasty. On the other hand, coronary bypass grafting and stringent downsizing of the mitral annulus by Physio rings 2 sizes smaller than measured have had promising results 7,8 with excellent competence of the mitral valve at the 2-year follow-up. This aggressive approach also provided for reverse remodeling of the left ventricle, which, presumably, is key to the long-term success of this approach.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] The conventional surgical treatment of severe mitral regurgitation in the absence of morphological abnormalities of the valve has been remodeling annuloplasty because coronary artery bypass grafting alone has led to a very high incidence of postoperative residual mitral regurgitation. 6 Unfortunately, although some investigators have reported good results, particularly with aggressive undersized annuloplasty, 7,8 other groups have experienced very high rates of recurrence of moderate or severe mitral regurgitation after such repairs. 9 -12 …”
mentioning
confidence: 99%
“…In contrast with these results, Braun and coworkers 4 reported that, in 87 patients undergoing restrictive ring annuloplasty (2 ring sizes, median ring size 26), no patient showing MR 3 and 2 with MR graded 2þ at 18-month follow-up. In addition, Geidel et al 28 …”
Section: Recurrence Of Mitral Regurgitationmentioning
confidence: 99%